Holothuroidea (Echinodermata) dos ecossistemas recifais do litoral central de Alagoas, Brasil - Miranda, Anderson Luiz Silva (2013)
The invertebrates on the class Holothuroidea are exclusively marine, call as sea cucumbers, and they are important components on reef ecosystems, which have largely perform in the much recycling of nutrients in the sediment of these and other coastal environments. However, the effect of Holothuroidea in marine communities is rarely documented, and suggesting that need for ecological studies on this group. Knowledge of class Holothuroidea on the Brazilian coast, particularly in reef ecosystems on the northeast is scarce. The present study describes the Holothuroidea species present in shallow reef ecosystems from Alagoas, including ecological and spatial distribution based on sediment characteristics as carbonates, organic matter and particle size. This study was conducted in nine reef ecosystems located in the central coast of Alagoas, with samples from intertidal zones up to 20m deep. The species identification was performed according to standard methodology and specific bibliography, as well as the sediment samples that were analyzed on the texture, organic matter and carbonates. The relationships between the distribution of Holothuroidea species and sediment characteristics were characterized by analyzed of Principal Component (PCA), Canonical Correspondence (ACC), Cluster analysis using UPGMA and Multidimensional Non Parametric (NMDS). In total, 17 species were identified from Holothuroidea, mostly found under rocks and in protected areas. Holothuria grisea had the highest occurrence in all reefs studied. Two other species were classified as common Synaptula hydriformis on the Ponta Verde coral reef and Trachythyone crassipeda the Riacho Doce coral reef. The analysis of the percentage of carbonates showed the greatest variation between the characteristics of the sediment. The cluster analysis indicated the formation of three groups with approximately 45% similarity, which was confirmed by NMDS, as well as CCAs demonstrated the influence of the sediment characteristics in the distribution of Holothuroidea species along the coral reefs on the central coastal Alagoas.